Opportunity Cost Neglect Attenuates the Effect of Choices on Preferences. (January 2016) - Greenberg, Adam Eric; Spiller, Stephen A.
The idea that choices alter preferences has been widely studied in psychology, yet prior research has focused primarily on choices for which all alternatives were salient at the time of choice. Opportunity costs capture the value of the best forgone alternative and should be considered as part of any decision process, yet people often neglect them. How does the salience of opportunity costs at the time of choice influence subsequent evaluations of chosen and forgone options? In three experiments, we found that there was a larger postchoice spread between evaluations of focal options and opportunity costs when opportunity costs were explicit at the time of choice than when they remained implicit.